Sensitive Scalp: A Possible Association With the Use of Hair Conditioners - Brenaut, Emilie; Misery, Laurent; Legeas, Cécile; Roudot, Alain-Claude; Ficheux, Anne-Sophie (Frontiers in Medicine, 2021)
A sensitive scalp is defined by the occurrence of unpleasant sensations (tingling, burning, pain, pruritus, tingling) triggered by stimuli that should not cause such sensations. Environmental factors, particularly cosmetics, can be triggering factors. The aims of this study were to assess hair cosmetic product consumption in subjects with sensitive scalp and to perform a clinical evaluation of sensitive scalp. After a dermatological examination, women between the ages of 18 and 65 years with or without a sensitive scalp completed different questionnaires. Their use of hair cosmetics (frequency, amount per application) was recorded. A total of 160 women with a mean age of 41 years were included. Twenty-seven patients presented with seborrheic dermatitis or psoriasis, so only 133 were included in the analysis. Five percent of the patients declared they had a very sensitive scalp, 25% had a sensitive scalp, 38% had a slightly sensitive scalp, and 32% had a scalp that was not sensitive. The mean sensitive scalp score (3S) score was 3.7 ± 1.6 in the very sensitive scalp group, 3.6 ± 2.1 in the sensitive group, 1.2 ± 1.2 in the slightly sensitive group and 0.1 ± 0.4 in the non sensitive group. Two groups were analyzed: the 56 subjects with a sensitive scalp (3S≥2 score) and the 56 subjects with a null 3S score. In the sensitive scalp group, 89% suffered from itch, and 45% suffered from tingling. No parameter (hormonal status, smoking, age, phototype, BMI) was associated with the 3S score. No differences in the exposure to shampoos and masks between the 2 groups were noted. The exposure to hair conditioners was significantly higher in the sensitive scalp group than in the group without sensitive scalp. Itch is the main symptom of a sensitive scalp. The frequency of a sensitive scalp was lower than that previously described when the subjects with scalp dermatosis were excluded. The amount of hair conditioners used was significantly higher in subjects with sensitive scalp than in those without sensitive scalp, suggesting a possible link.